Multi-Omics Analysis Revealed the Accumulation of Flavonoids and Shift of Fungal Community Structure Caused by Tea Grafting (Camellia sinensis L.) - Liu, Yue; Liu, Jun; Tian, Yiping; Ye, Shuang; Pang, Dandan; Chen, Linbo; Qu, Hao (Plants (Basel), 2025)
Grafting is an important approach to improving tea plant varieties, and tea grafting can result in changes in secondary metabolites. However, the shifting pattern of secondary metabolites between scions, rootstocks, and non-grafted tea leaves is unclear. We employed “Yuncha 1” as the scion and “Zijuan” as the rootstock with significant differences in leaf color traits to reveal the influences of grafting on the generation of secondary metabolites and transcriptional activities. By non-targeted metabolomic analysis, we identified that grafting led to an obvious shift in secondary metabolites between the scion, rootstock, and non-grafted tea leaves. Importantly, we found that grafting significantly enhanced the accumulation of flavonoids, the vital component of secondary metabolites for the flavor quality, purple color, and health-beneficial effect of Zijuan tea. Via transcriptomics, we found that the key biosynthetic genes DFR and EC 1.1.1.219 for synthesizing flavonoids were significantly enhanced in rootstock compared with non-grafted Zijuan. Concurrently, ANS for biodegrading flavonoids was significantly suppressed in rootstock compared with non-grafted Zijuan. These results revealed the shifting mechanism of key secondary metabolites during grafting. In addition, we found that the shift after grafting possessed no significant influence on bacterial community diversity, but grafting slightly enhanced the fungal community diversity of scions. We found that the shift in fungal community diversity was driven by rootstocks with a higher fungal community diversity. This study systematically reveals the shift in secondary metabolites and fungal community diversity, which provides a novel and comprehensive understanding and theoretical basis for plant breeding using grafting.